Syariah Principles in Culinary Marketing: A Dialectical Study of Profitability and Business Morality - Arif Budiman; Wargo; Nurjali; Erwina Kartika Devi (CV. Civiliza Publishing, 2026)
The culinary industry in the modern era is characterized by hyper-competition, often leading business practitioners to prioritize short-term profitability over ethical considerations, which results in deceptive marketing practices. This study aims to analyze the dialectical relationship between profitability and business morality by examining the marketing strategies of the Pagi Sore eatery in Talang Babat from the perspective of Islamic business ethics. Employing a descriptive-qualitative case study approach, data were gathered through in-depth interviews, passive participant observation, and documentation studies, subsequently analyzed using an interactive model of data reduction and inductive reasoning. The results demonstrate that the eatery successfully internalizes prophetic values shiddiq (truthfulness), amanah (trustworthiness), fathanah (wisdom), and tabligh (advocacy) into its marketing mix, particularly through halalan thoyyiban product assurance and transparent pricing. Crucially, the findings reveal a